2010
DOI: 10.1117/12.848704
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive condition assessment of bridge decks by multimodal NDE

Abstract: Corrosion induced bridge deck delamination is a common problem in reinforced concrete decks. While condition assessment can be done using a number of traditional and NDE methods, the presented study concentrates on a complementary use of five NDE techniques: impact echo (IE), ground penetrating radar (GPR), half-cell potential (H-C), ultrasonic surface waves (USW) and electrical resistivity (ER). Each of the five techniques has its advantages and limitations. However, each of them can contribute to a more comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…The results varied from study to study. Some studies found good correlation between the NDT methods being tested (Gucunski et al, 2010;Oh et al, 2013), while other studies found that the results from the different methods varied significantly (Donnelly et al, 2012;Scott et al, 2002), which of course shows that no one method is perfect in every application. The findings from these studies collectively suggest that using multiple NDTs is a better approach to correctly characterize the deterioration in the deck.…”
Section: Benefits Of Using Complementary Nondestructive Testing Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results varied from study to study. Some studies found good correlation between the NDT methods being tested (Gucunski et al, 2010;Oh et al, 2013), while other studies found that the results from the different methods varied significantly (Donnelly et al, 2012;Scott et al, 2002), which of course shows that no one method is perfect in every application. The findings from these studies collectively suggest that using multiple NDTs is a better approach to correctly characterize the deterioration in the deck.…”
Section: Benefits Of Using Complementary Nondestructive Testing Methodsmentioning
confidence: 99%
“…Although past studies investigated using HCP on epoxy-coated rebar, it is still recommended that its use should be limited to uncoated rebar. Cover, moisture, temperature, and chloride ion concentrations can all affect the results (Gucunski et al, 2010).…”
Section: Appendices Appendix A: Literature Review Of Ndt Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this SAGEEP 2013 Denver, Colorado USA http://www.eegs.org reduction in the reflected amplitude at the reinforcement is often used more qualitatively as an indicator for the health of the bridge deck. Many researchers and practitioners endeavor to interpret GPR data to gain an understanding of the deterioration of the bridge decks (Gucunski et al, 2010;Amos, 2009) and even the presence of rust on the reinforcement using experimental GPR data Martino et al, 2012). One key aspect is to relate the electromagnetic properties of concrete in various states of deterioration or corrosion to deteriorated conditions.…”
Section: Sageep 2013mentioning
confidence: 98%